PRDX2 Protects Against Atherosclerosis by Regulating the Phenotype and Function of the Vascular Smooth Muscle Cell - Li, Jing; Wang, Cong; Wang, Wenjing; Liu, Lingzi; Zhang, Qingqing; Zhang, Jun; Wang, Bo; Wang, Shujing; Hou, Li; Gao, Chuanzhou; Yu, Xiao; Sun, Lei (Frontiers in Cardiovascular Medicine, 2021)
Peroxiredoxin 2 (PRDX2), an inhibitor of reactive oxygen species (ROS), is potentially involved in the progression of atherosclerosis (AS). The aim of this study was to explore the role and mechanism of PRDX2 in AS. The expression of PRDX2 was evaluated in 14 human carotid artery tissues with or without AS. The results showed that the positive reaction of PRDX2 was observed in the carotid artery vascular smooth muscle cells (CAVSMCs). To assess the mechanism by which PRDX2 may function in AS, the CAVSMCs were transfected with pEX4-PRDX2 and si-PRDX2. The catalase, hydrogen peroxide (H2O2) scavenger, was used to further confirm that PRDX2-induced inhibitory effects might be mediated through reducing ROS levels. Phenotype alteration and functional testing included transcription testing, immunostaining, and expression studies. The drug of MAPK signaling pathway inhibitors SB203580, SP600125, and PD98059 was used to evaluate the underlying mechanism. In this study, we found that the protein level of PRDX2 and the level of H2O2 were higher in the human AS carotid artery tissues than in the normal carotid artery tissues, accompanied with the activation of MAPK signaling pathway. The up-regulation of PRDX2 in the CAVSMCs significantly decreased the expression of ROS, collagen type I (COL I), collagen type III (COL III), vascular cell adhesion molecule-1 (VCAM-1), and intercellular adhesion molecule-1 (ICAM-1) and inhibited the proliferation, migration, and transformation of the CAVSMCs. The up-regulation of PRDX2 reversed the effect of the CAVSMCs treated with tumor necrosis factor-α (TNF-α). In addition, PRDX2 down-regulation promoted the protein levels of p-p38, p-JNK, and p-ERK, which was confirmed in relevant MAPK inhibitor treatment experiments. Our results suggest a protective role of PRDX2, as a scavenger of ROS, in AS progression through inhibiting the VSMC phenotype alteration and function via MAPK signaling pathway.